Conflict and peace-building in Africa: The regional dimensions - Timothy M. Shaw (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
Contemporary Africa reveals a range of causes, consequences and responses to conflicts which are increasingly interrelated as well as regional in character, as around the Great Lakes/Horn. Their economic and non-state features are undeniable, leading to some promising possibilities in terms of `track-two' diplomacy both on and off the continent, such as the `Kimberley Process' around `blood' diamonds. Development corridors and trans-frontier peace-parks may also constitute innovative ways to moderate and contain conflict. As often, changeable African cases challenge established assumptions, analyses and policies, such as those around civil society, governance, regional and security studies.
Keywords: O55; O10; N47; 330; sub-Saharan Africa; conflict; peace-building